Search 75,981 tutors
FIND TUTORS
Ask a question

Answers by Bill L.

Homer and Mike were replacing on mikes old deck. Mike can do the job in one hour less than Homer. they worked together for three hours until Homer had to go home. Mike finished the job working by himself for an additional 4 hours. How long would it have taken Homer to finish the deck by himself Let...

log(x-5) + log(x-2) = 1 log((x-5)(x-2)) = 1 (x-5)(x-2) = 10^1 (x-5)(x-2) = 10 x^2-7x+10 = 10 x^2-7x = 0 x(x-7) = 0 x = {0, 7} 0 is an "extraneous" solution because you cannot plug it back into the original equation. Solution: x = 7  ...

y^3 z^6/y^5 z^6 (answer)

(y^3 z^6)/(y^5 z^6) since there are more y's in the denominator, we move the y's from the numerator to the denominator: (z^6)/(y^5 y^(-3)z^6) (z^6)/(y^(5-3)z^6) (z^6)/(y^2z^6) the z's all cancel leaving: 1/y^2

Given: h= -16t^2+64t+512 Set h to 0 and solve for t: 0 = -16t^2+64t+512 multiplying both sides by 1: 0 = 16t^2-64t-512 dividing both sides by 16: 0 = t^2-4t-32 factoring: 0 = (t+4)(t-8) t = {-4, 8} throw out the negative solution (extraneous)...

I presume they are asking you to derive the equation of the line that has: slope of 6 and a y intercept of -3 Method 1: "Slope-intercept" of a line: y = mx + b where m is the slope and b is the y-intercept plug in the given data and you're done: y = 6x +...

Find x if the slope between (7,-9) and (x,-13) is -1/3 slope between two points: slope = (y2 - y1)/(x2 - x1) plug the given data from the problem and solve for x: -1/3 = (-13 - (-9))/(x - 7) -1/3 = (-13 + 9)/(x - 7) -1/3 = (-4)/(x - 7) cross -multiplying: 3(-4)...

1/3(x + 9) = 12 (answer)

Solving for x: 1/3(x + 9) = 12 multiply both sides by 3 to remove the denominator: (3)(1/3(x + 9)) = (3)12 (x + 9) = 36 subtracting 9 from both sides: x + 9 - 9 = 36 - 9 x = 27

From Pythagorean identities: 1 + tan^2 x = sec^2 x and tan^2 x = sin^2 x/cos^2 x   So, now instead of 2 tan x / (1 + tan^2 x) we have: 2(sin^2 x/cos^2 x) / sec^2 x but 1/cos^2 x = sec^2 x 2(sin^2 x *sec^2 x) / sec^2 x 2(sin^2 x) &nbs...

a. computer capacity is often measured in bits and bytes. a bit is the smallest unit, which is 1 or 0, in the computer's memory. a bytes is 2^3 bits. a megabyte (mb) is 2^20 bytes. how many bits are in a megabytes? 2^20 * 2^3 = 2^(20+3) = 2^23 b. a gigabyte (gb) is 2^30 bytes. how many...

Smile more and make it a point to say hello to people.  You break the ice first.  Start/participate in study groups. Be active in school -- participant in student government, join service clubs, clubs pertaining to your interest, or join sports program, etc. Good luck...

Starting with: [9m^2-1]/[3m+3] factoring the denominator: [9m^2-1]/[3(m+1)] rewriting the numerator as: [(3m)^2-1^2]/[3(m+1)]  "difference of squares" -- special case factoring [(3m-1)(3m+1)]/[3(m+1)] canceling like-terms: (3m-1)/3 or m...

(TanX)-1)/(Tan(X)+1) = (1-cot(X))/(1+cot(X)) Let's make the "right side" of the equation look like the left: (1-cot(X))/(1+cot(X)) since cot(x) = 1/tan(x) we can rewrite as: (1-1/tan(x))/(1+1/tan(x)) (1-1/tan(x))/(1+1/tan(x)) * tan(x)/tan(x) (tax(x)-1)/(tan(x)+1) ...

6x-5>4x-1= (answer)

Isolate the unknown to one side of the inequality: 6x-5>4x-1 subtracting 4x from both sides: 2x-5 > -1 adding 5 to both sides: 2x > 4 dividing both sides by 2: x > 2 To graph on a number line: place an OPEN dot at 2 solid line from the dot and...

3(x+2)-2(y+1) if x=2 and y =2 substitute x for 2 and substitute y for 2: 3(2+2)-2(2+1) apply "order of operations" -- parentheses first: 3(4)-2(3) multiplication next: 12-6 6

2x+1-y+2 if x=1 and y=2 start with: 2x+1-y+2 substitute x for a 1 and substitute y for a 2: 2(1)+1-2+2 2+1-2+2 3-2+2 1+2 3